2016
DOI: 10.4038/jas.v11i1.8076
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Assessment of the Antibacterial Activity in Fruit Juice of Sri Lankan Sweet Orange Cultivars vis a vis Sour Orange

Abstract: Sweet orange (Citrus sinensis), a key fruit species, is considered as a primary ingredient in herbal medical formulations against ailments such as food borne diseases. Sour orange (C. aurantium) is also very famous as a medicinal plant. There are six commonly grown sweet orange cultivars in Sri Lanka (Arogya, Bibila sweet, MKD, Sisila, BAN and MT) but the antibacterial activity present in their fruit juice is not well documented. Therefore, the present study was conducted to characterize the antibacterial acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Asian countries are famous for traditional medical practices such as Ayurveda, Unani, and Siddha [1]. Medicinal plants have been a valuable source of natural active constituents that products used for maintaining human health and treatment of many human diseases [2].…”
Section: Introductionmentioning
confidence: 99%
“…Asian countries are famous for traditional medical practices such as Ayurveda, Unani, and Siddha [1]. Medicinal plants have been a valuable source of natural active constituents that products used for maintaining human health and treatment of many human diseases [2].…”
Section: Introductionmentioning
confidence: 99%
“…Sour orange or bitter orange (pH of 2 to 2.6) is quite popular in Asian countries where all parts of this fruit have traditionally been utilized as herbal medicine [ 44 , 45 ]. In general, citrus fruits including sour orange are mainly composed of organic acids and sugars, though also have bioactive compounds, such as hydrocinnamic acid, ferulic acid, hesperidin, cyanidin glucoside, vitamin C, carotenoid, and naringin (responsible for the bitter taste), which provide special health benefits [ 46 ].…”
Section: Introductionmentioning
confidence: 99%
“…In general, citrus fruits including sour orange are mainly composed of organic acids and sugars, though also have bioactive compounds, such as hydrocinnamic acid, ferulic acid, hesperidin, cyanidin glucoside, vitamin C, carotenoid, and naringin (responsible for the bitter taste), which provide special health benefits [ 46 ]. Antibacterial properties of different kinds of citrus species have been investigated mostly focusing on the antibacterial activity of peel essential oils [ 45 , 47 , 48 , 49 ]. It was demonstrated that different sweet and sour orange cultivars may show different antibacterial behavior [ 45 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Drugs which are derived from natural sources have a significant role in the prevention and treatment of infections in humans. Hence, there is a need to search for new strategies to fight and control microbial infections [6].…”
Section: Introductionmentioning
confidence: 99%